ANNONACEAE DI TAMAN NASIONAL BOGANI NANI WARTABONE: STUDI PENDAHULUAN KEANEKARAGAMANNYA - Rugayah Rugayah; Deni Sahroni; Dirman Dirman (PTTI, 2011)
Rugayah, Deni Sahroni & Dirman. 2011. Annonaceae in Bogani Nani Wartabone National Park: A Preliminary Study on its Diversity. Floribunda 4(2): 40–47. — Annonaceae is one of important family in low land forest in Malesia. It is noted that some species have economic value as perfume and also edible fruit. This study is based on herbarium specimens kept in Herbarium Bogoriense. There were 18 species belongs to 12 families, which have been collected from Bogani Nani Wartabone National Park, North Sulawesi. Orophea hexandra was reported as a new record for Sulawesi, Pseuduvaria oxycarpa and Mitrephora ferrugenea was reported as endangered species. Identification key to the genera and species and their distribution were presented in this paper.